PENGARUH KUALITAS PELAYANAN DAN CITA RASA PRODUK TERHADAP KEPUTUSAN PEMBELIAN ULANG PRODUK - Frans Andreas, Yosua; Alfatera Unpapar, Aldrich (Jurnal Indonesia Sosial Sains, 2021)
This research aims to determine and explain the effect of Service Quality (X1) and Taste (X2) on Repurchase Decisions (Y), either in partially or simultaneously. The descriptive statistical analysis and multiple linear regression analysis engaged to analyze data. The data in this study were processed by IBM SPSS software version 26. The results showed that there were positive and significant influence between the Service Quality variable (X1) on the Repurchase Decision (Y), and  positive and significant influence between the Taste (X2) variables on the Repurchase Decision (Y), also all the independent variables was verified that  have an effect on the dependent variable silmutaneously.